REDEFINING LEARNING PROCESS THROUGH FLIPPED CLASSROOM - Fauzi, Adin (Universitas Islam Balitar, 2019)
This study addresses the implementation of the flipped classroom in redefining the traditional learning process in higher education. The data were collected by observing the learning process of Advanced Listening course, which was set up in a flipped classroom mode. The data of observation showed that the steps in the flipped classroom were as follows: (1) learning the materials (beyond the classroom); (2) taking notes and preparing questions (beyond the classroom); (3) presenting the materials (inside the classroom); and (4) discussing the materials (inside the classroom). The findings suggest that educators should start flipping the classroom since it provides a lot of educational benefits.